Direct rapid tooling for polymer processing using sheet metal tools - Afonso, D. (2017)
The rapid tooling notion has been discussed since the beginning of the additive manufacturing processes. The concept consists on using fast manufacturing technologies to develop tools to process other materials. New incremental sheet metal forming processes operation allows a parity to the former rapid prototyping perception, and so feasibly considered a smart manufacturing process. This processes encounter industrial applications not only in prototyping and part manufacturing but also in tool development and fabrication. This paper discuss the fundamentals of the rapid tooling concept and presents four examples of the use of incremental forming for the development of sheet metal moulds. The research concludes with a proof of concept for the use of rapid sheet metal tools for processing thermoplastics and thermosets. The use of incremental forming as a rapid tooling technology contributes to decrease the time to market, decrease tooling cost and increase tooling complexity and consequential part design freedom.